SYMBOLIC POWER AND EMPLOYEE SILENCE IN HIGHER EDUCATION: NAVIGATING MALAY RIAU CULTURAL VALUES FOR ORGANIZATIONAL TRANSFORMATION - Muhammad Gaza Wiriadi; Riani Rachmawati (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study explores the dynamics of power relations and employee silence within a higher education institution in Riau, Indonesia, deeply rooted in Malay cultural values. While modern organizations aim for sustainable transformation through meritocracy, local cultural values such as "segan" (reluctance/respect), "adab" (manners), and loyalty create a complex symbolic power structure. Using a qualitative interpretative phenomenological approach, data were collected through in-depth interviews with junior and senior lecturers. The findings reveal that power operates symbolically rather than coercively. Employee silence is not merely passive submission but a strategic "prosocial silence" to maintain collective harmony and respect senior authority. However, this cultural silence poses challenges to organizational transformation by inhibiting critical feedback and creating "defensive silence" among junior staff. The study contributes to the Human Capital Management literature by highlighting how local wisdom can be negotiated to balance cultural harmony with the demands of professional organizational transformation.